Analisis Perilaku terhadap Niat Berinvestasi - Khaerudin Sidik Patoni; Nurjanna Ladjin; Eva Yuniarti Utami; Alfiana; Natal Kristiono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine and analyze the influence of behavior on investor intentions. This study uses primary data. The sample used was 100 respondents, namely people who have invested, have worked and have a fixed income. The sampling technique used nonprobability sampling, precisely the respondent accidental technique by distributing questionnaires. This type of research is quantitative research, then the data was analyzed using research instrument tests (validity and reliability tests), multicollinearity tests, multiple regression analysis (regression models, determination coefficients, F tests, t tests), and classical assumption tests (heteroscedasticity tests, normality, assistance and autocorrelation) with the SPSS software program version 25.0. The results showed that financial behavior has a positive and significant effect on investment intentions. This shows that the better a person's level of financial behavior, the better their investment intentions will be. Investment knowledge has a positive and significant effect on investment intentions. This shows that the better a person's level of investment knowledge, the better their investment intentions will be. Financial literacy has a positive and significant effect on investment intentions. This shows that the better a person's level of financial literacy, the better their investment intentions will be.